Імунотерапія хворих на метаболічний синдром - Скрипник, Н. В. (Clinical Endocrinology and Endocrine Surgery, 2009)
This manual article deals with peculiarities of immunological status of patients suffering from diabetes mellitus with metabolic syndrome. The degree of immunopathological changes depends on the complexity and duration of the disease and serve as a prognostic criterion for a development of complications of type 2 diabetes. Influence of timomimetic "Immunofan" (Scientific Manufacturing Enterprise "BIONOX", Russian Federation) on patients with type 2 diabetes with persistent immunological disorders was analised. Pharmacocinetics the substantiation of its long application for the given group of patients in combination with basic therapy are shown. The effectiveness, safety and pathogenetic influence of "Immunofan" on patients with type 2 diabetes were proved. The drug reliably normalizes indices of cellular, humoral immunity, improves the quality of phagocytosis in patients suffering from diabetes mellitus with metabolic syndrome. Present day possibilities of immunodiagnostics allow to detect the immune dysfunction in time, and the immune correcting medicine "Immunofan" can effectively potentiate the basic treatment and secondary prophylaxis at metabolic syndrome.